Investigation of Protein Biomarkers and Oxidative Stress in Pinirampus pirinampu Exposed to Mercury Species from the Madeira River, Amazon-Brazil - Vieira, José Cavalcante Souza [UNESP] (2022)
In recent decades, the scientific community has widely debated the contamination of fish in the Amazon region by mercury species. As the diet of riverside populations in the Amazon region is based mainly on fish, these populations are exposed to mercurial species that can cause serious and irreversible damage to their health. The risks of consuming fish exposed to mercurial species in the Amazon region have motivated toxicological investigations. However, the effect of mercurial species on protein and enzyme levels is still controversial. In this work, analytical and bioanalytical techniques Two-dimensional polyacrylamide gel electrophoresis [2D-PAGE] Graphite Furnace Atomic Absorption Spectrometry [GFAAS], and Mass Spectrometry in Sequence with Electrospray Ionization [ESI–MS/MS] were used to identify proteins associated with mercury (metal-binding protein) in muscle and liver tissues of the fish species Pinirampus pirinampu from the Madeira River, in the Brazilian Amazon. Enzymatic and lipid peroxidation analyses were also used to assess changes related to oxidative stress. Determinations of total mercury by GFAAS indicated higher concentrations in liver tissue (555 ± 19.0 µg kg−1) when compared to muscle tissue (60 ± 2.0 µg kg−1). The fractionation process of tissue proteomes by 2D-PAGE and subsequent mapping of mercury by GFAAS in the protein spots of the gels identified the presence of mercury in three spots of the liver tissue (concentrations in the range of 0.800 to 1.90 mg kg−1). The characterization of protein spots associated with mercury by ESI–MS/MS identified the enzymes triosephosphate isomerase A, adenylate kinase 2 mitochondrial, and glyceraldehyde-3-phosphate dehydrogenase as possible candidates for mercury exposure biomarkers. The muscle tissue did not show protein spots associated with mercury. Enzymatic activity decreased proportionally to the increase in mercury concentrations in the tissues. Graphical abstract: [Figure not available: see fulltext.]